Indigenous Genocidal Tracings: Slavery, Transracial Adoption, and the Indian Child Welfare Act - de Bourbon, Soma Leo (eScholarship, University of California, 2013)
ABSTRACT Indigenous Genocidal Tracings: Slavery, Transracial Adoption, and the Indian Child Welfare Act by Soma de Bourbon Indigenous Genocidal Tracings: Slavery, Transracial Adoption, and the Indian Child Welfare Act is a feminist, interdisciplinary history that traces the genealogy of U.S. property interests in Indigenous people from enslavement to the continued transracial adoption of Native children. The interconnection of Native history with that of Black Americans is interrogated, paying critical attention to the ways in which both communities continue to suffer overrepresentation in prisons, jails, juvenile detention centers, reproductive control programs, and child welfare systems (foster and adoptive care).In contrast to the work on Native transracial adoption (TRA) that has focused almost exclusively on outcome, the dissertation argues that Native TRA constitutes a group-based harm and situates it within the active process of settler colonialism and genocide. Specific attention is paid to slavery, land dispossession, boarding schools, adoption programs (such as the Indian Adoption Project and the Mormon Placement Program), and the creation of "unfit" women and "unwanted" children. Drawing on the Association on American Indian Affairs archives, the dissertation argues that the ways in which putatively "unfit" Native women fought back were the impetus for one of the most important federal Indian laws ever passed by Congress, The Indian Child Welfare Act (ICWA).The dissertation's chapters investigate the history of ICWA and the ways that state courts continue to violate ICWA's intentions by circumventing it through judicially created exceptions such as the Existing Indian Family. Through personal interviews with members of the Christian Alliance for Indian Child Welfare (CAICW), an organization that works to defeat ICWA, the author highlights the way CAICW's work can be seen as an example of the current landscape of ownership over Native people. Indigenous Genocidal Tracings ends with the work of the First Nations Repatriation Institute and its Director and co-founder Sandy White Hawk to illustrate not only the amazing survivance of Native people, but also the fact that Native people continue to find Native-centered ways of ameliorating the harmful effects of transracial adoption and colonization.